2020
DOI: 10.33448/rsd-v9i8.5953
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da biocompatibilidade do polímero PCL recobrindo a liga Ti-30Ta

Abstract: Nos últimos anos, diversas pesquisas têm sido realizadas buscando o desenvolvimento de materiais para aplicações biomédicas. E, um dos objetivos desses estudos, é otimizar o comportamento da interface material/meio biológico. Dentre os materiais mais utilizados, estão o titânio e suas ligas devido às suas propriedades como resistência à corrosão e biocompatibilidade. Estudos constataram que o comportamento celular pode ser influenciado por alterações na morfologia das superfícies. Dessa maneira, o objetivo des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Por este motivo, o ensino da química é fundamental para o progresso da sociedade, principalmente em questões ambientais e sustentáveis (Capellato;Ribeiro;Sachs, 2019).…”
Section: Introductionunclassified
“…Por este motivo, o ensino da química é fundamental para o progresso da sociedade, principalmente em questões ambientais e sustentáveis (Capellato;Ribeiro;Sachs, 2019).…”
Section: Introductionunclassified
“…(Chai et al, 2008;López et al, 2001) The modification the surface can promote improvement the corrosion resistance the material, increase of the bioactivity characteristic of the titanium oxides formed spontaneously on the surface, presenting promising results in the interaction with the tissue, since the biocompatibility (inertiality or bioactivity) is determined by chemical processes occur at the interface between the prosthesis and the living tissue. (Capellato, 2020;Chen et al, 2013;Geetha et al, 2009;Mohammed et al, 2015;Rungsiyakull et al, 2010) One of the most promising surface modifications is laser beam irradiation, a technique that consists of providing a large irregularity on the surface the material in a '' clean '' manner to create a morphology with a large specific area and physical properties-chemicals suitable for promoting the interaction of apatites and providing the formation of a great diversity of oxides aiming induce the phenomenon of osseointegration more effectively and satisfactorily. (Queiroz et al, 2013;Valente, 2017) Some researchers, in a study using Nd; YAG lasers, found that implants with surfaces modified by laser beam, present better and more stable fixation to the bone in relation to the machined ones, and attributes this characteristic to the oxidation process of the surface contributing to a favorable way for the osseointegration process, providing increased hardness and corrosion resistance, as well as improved wettability and increased free surface energy.…”
Section: Introductionmentioning
confidence: 99%